953 PREVIOUS SARS-COV2 INFECTION, AGE AND FRAILTY PREDICT 6-MONTH BNT162B2 VACCINE-INDUCED ANTIBODY TITRE IN NURSING HOME RESIDENTS. (14th June 2022) - Dyer, A; Noonan, C; Pierpoint, R; Leonard, A; Boran, G; Brady, G; Fallon, A; O'Farrelly, C; Bourke, N; Kennelly,
Abstract: Introduction: Older nursing home residents are the population at greatest risk of morbidity and mortality from SARS-CoV-2 infection. No studies have examined the determinants of long-term antibody responses post-vaccination in this group. Method: Longitudinal cohort study in residents of 5 nursing homes assessed prior to vaccination and at both 5-weeks and 6-months post SARS-CoV2 vaccine (BNT162b2). Comprehensive clinical assessment was performed, including assessment for comorbidity, frailty (NH-FRAIL) and SARS-CoV-2 infection history. Serum Nucleocapsid and Anti-Spike Receptor Binding Domain (RBD) antibodies were analysed at all timepoints and an in vitro Angiotensin Converting Enzyme (ACE2) Receptor-Spike RBD neutralisation assay used to assess serum neutralisation capacity. Results: Of 86 participants (81.1 ± 10.8 years; 65% female), just-under half (45.4%; 39/86) had evidence of previous SARS-CoV-2 infection. All participants demonstrated a significant antibody response to vaccination at 5-weeks and a significant decline in this response by 6-months. SARS-CoV-2 infection history was the strongest predictor of antibody titre (log-transformed) at both 5-weeks (β : 3.00; 95% CI [Confidence Interval]: 2.32, 3.70; p < 0.001) and 6-months (β : 3.59; 95% CI: 2.89, 4.28; p < 0.001). Independent of SARS-CoV-2 infection history, both age in years (β : -0.05; 95% CI: −0.08, −0.02; p < 0.001) and frailty (β : -0.22; 95% CI: −0.33, −0.11; p < 0.001) were associated with a lower antibody titre at 6-months. Antibody titres at both 5-weeks and 6-months significantly correlated with in vitro neutralisation capacity. Conclusion and Implications: In older nursing home residents, SARS-CoV-2 infection history was the strongest predictor of anti-spike antibody titres at 6-months, whilst age and frailty were independently associated with lower titres at 6-months. Antibody titres significantly correlated with in vitro neutralisation capacity. Whilst older SARS-CoV-2 naïve nursing home residents may be particularly vulnerable to breakthrough SARS-CoV-2 infection, the relationship between antibody titres, SARS-CoV-2 infection and clinical outcomes remains to be fully elucidated in this cohort.